Occupational asthma due to chrome and nickel electroplating. Issue 1 (January 1997) - Bright, P; Burge, P S; O'Hickey, S P; Gannon, P F; Robertson, A S; Boran, A
Abstract : BACKGROUND: Exposure to chromium during electroplating is a recognised though poorly characterised cause of occupational asthma. The first series of such patients referred to a specialist occupational lung disease clinic is reported. METHODS: The diagnosis of occupational asthma was made from a history of asthma with rest day improvement and confirmed by specific bronchial provocation testing with potassium dichromate and nickel chloride. RESULTS: Seven workers had been exposed to chrome and nickel fumes from electroplating for eight months to six years before asthma developed. One subject, although exposed for 11 years without symptoms, developed asthma after a single severe exposure during a ventilation failure. This was the only subject who had never smoked. The diagnosis was confirmed by specific bronchial challenges. Two workers had isolated immediate reactions, one a late asthmatic reaction, and four a dual response following exposure to nebulised potassium dichromate at 1-10 mg/ml. Two of the four subjects were also challenged with nebulised nickel chloride at 0.1-10 mg/ml. Two showed isolated late asthmatic reactions, in one at 0.1 mg/ml, where nickel was probably the primary sensitising agent. Four workers carried out two hourly measurements of peak expiratory flow over days at and away from work. All were scored as having occupational asthma using OASYS-2. Breathing zone air monitoring was carried out in 60 workers from four decorative and two hard chrome plating shops from workers with similar jobs to those sensitised. No measurement exceeded the current occupational exposure standard for chromate or nickel, the mean levels of chromate exposure for jobs similar to those of the affected workers were 9-15 micrograms/m3. CONCLUSION: Chrome used in electroplating is a potential cause of occupational asthma. Sensitivity to chrome in electroplaters may occur in situations where exposure levels are likely to be within the current exposure standards. There may be cross reactivity with nickel. Inhalation challenge with nebulised potassium dichromate solution is helpful in making the specific diagnosis where doubt exists.